2021
DOI: 10.3390/atmos12121549
|View full text |Cite
|
Sign up to set email alerts
|

Has COVID-19 Lockdown Affected on Air Quality?—Different Time Scale Case Study in Wrocław, Poland

Abstract: Due to the COVID-19 pandemic, there are series of negative economic consequences, however, in limiting mobility and reducing the number of vehicles, positive effects can also be observed, i.e., improvement of air quality. The paper presents an analysis of air quality measured by concentrations of NO2, NOx and PM2.5 during the most restrictive lockdown from 10 March to 31 May 2020 on the case of Wrocław. The results were compared with the reference period—2016–2019. A significant reduction in traffic volume was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, the predicted concentrations of PM 2.5 and PM 10 in Shanghai were higher by an average of 60.81% and 43.12% per day, respectively compared to the observed values throughout the lockdown period from 31 March to 1 June 2022. Therefore, COVID-19 lockdown measures in Shanghai can be considered to have a positive impact on air quality, which is similar to the findings of some public studies researching the changes in the levels of PM 2.5 and PM 10 during the lockdown [9,15,[17][18][19][20]. However, unlike other studies, our study regarded predicted concentrations of PM 2.5 and PM 10 during the lockdown period as the concentrations without lockdown measures.…”
Section: Comparison Of Prediction Results With and Without Meteorolog...supporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, the predicted concentrations of PM 2.5 and PM 10 in Shanghai were higher by an average of 60.81% and 43.12% per day, respectively compared to the observed values throughout the lockdown period from 31 March to 1 June 2022. Therefore, COVID-19 lockdown measures in Shanghai can be considered to have a positive impact on air quality, which is similar to the findings of some public studies researching the changes in the levels of PM 2.5 and PM 10 during the lockdown [9,15,[17][18][19][20]. However, unlike other studies, our study regarded predicted concentrations of PM 2.5 and PM 10 during the lockdown period as the concentrations without lockdown measures.…”
Section: Comparison Of Prediction Results With and Without Meteorolog...supporting
confidence: 83%
“…Besides, reductions in surface PM 2.5 and PM 10 were reported in six mega-cities in India during the lockdown period [18,19]. In 2020, PM concentrations at the traffic and background stations are on average 15% and 13.4% lower than in the reference period in Wrocław, Poland [20]. In contrast, in Italy, no decrease in particulate matter (PM 10 or PM 2.5 ) was observed during the first phase of the COVID-19 epidemic [21] and Few sites (2-3 out of 16) experienced statistically significant drops in PM 2.5 in Ontario, Canada [22].…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of the blockade affected the reduction of motor vehicle traffic. As indicated by studies conducted in other Polish cities during the COVID-19 pandemic, traffic at major intersections dropped by several tens of percent compared to 2019, the time before the pandemic, including in Krakow by 40% [ 78 ] and in Wroclaw by almost 30% [ 79 ]. As seen in Table 7 , most of the investigated roads were of the national and provincial type.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [11] assessed the effect of different emergency response levels on air quality in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA), and found that the concentration of PM 2.5 , PM 10 , NO 2 , CO, and O 3 were not significantly different during the Level II and III response periods. Tomasz Turek et al [12] demonstrated that restricting anthropogenic activities did not have an impact on long-term changes and trends in air quality in Wroclaw, Poland. In contrast, Elçin Tan [13] found that the average air quality in Istanbul improved by about 17% during the long-term lockdown period (12 March 2020 to 30 June 2021).…”
Section: Introductionmentioning
confidence: 99%